2011
DOI: 10.1002/hep.24493
|View full text |Cite
|
Sign up to set email alerts
|

Aldo-keto reductase-7A protects liver cells and tissues from acetaminophen-induced oxidative stress and hepatotoxicity

Abstract: Aldo-keto reductase-7A (AKR7A) is an enzyme important for bioactivation and biodetoxification. Previous studies suggested that Akr7a might be transcriptionally regulated by oxidative stress-responsive transcription factor nuclear factor erythroid 2 p45-related factor 2 (Nrf2), a protein highly responsive to acetaminophen (APAP) or its intermediate metabolite, N-acetyl-p-benzoquinoneimine (NAPQI). This study was, therefore, carried out to investigate whether Akr7a is involved in the protection against APAP-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 49 publications
5
26
0
Order By: Relevance
“…We previously demonstrated in APAP-induced hepatotoxicity that overexpression of aldo-keto reductase-7a (AKR7A) in HepG2 caused significant hepatoprotection against APAP-induced oxidative stress and cell death [14]. In the present study, we have shown that APAP-induced hepatotoxicity and increased expression levels of aldose reductase in AML-12, and plasmid overexpressing aldose reductase augmented APAP induced oxidative stress and cell death.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We previously demonstrated in APAP-induced hepatotoxicity that overexpression of aldo-keto reductase-7a (AKR7A) in HepG2 caused significant hepatoprotection against APAP-induced oxidative stress and cell death [14]. In the present study, we have shown that APAP-induced hepatotoxicity and increased expression levels of aldose reductase in AML-12, and plasmid overexpressing aldose reductase augmented APAP induced oxidative stress and cell death.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, inhibition of aldose reductase renders J774A.1 macrophage cell line more susceptible to acrolein or hydrogen peroxide-induced cell death [17]. Also we previously demonstrated that increased AKR7A3 in HepG2 cells was associated with the up-regulation of oxidative stress-related enzymes to enhance cellular antioxidant defense, which appeared to contribute significantly to protection against APAP-induced toxicity [14]. Therefore, we suggest that aldose reductase may provide a mechanism for the cellular detoxification of APAP.…”
Section: Discussionmentioning
confidence: 68%
“…39,46 The human AKR genes AKR1B1 , AKR1B10 , AKR1C1 , AKR1C2 , AKR1C3 , AKR7A2 , and AKR7A3 are all regulated by the Keap1/Nrf2 system. 7,9,10,4752 Although many studies measure NQO1 induction as a read out of Nrf2 activation, often the level of induction of NQO1 is a quite modest 2–3 fold by comparison to the induction seen in the AKR genes, which can be 1–2 orders of magnitude greater. 52,53 In fact, the AKR gene response can be one of the most robust signatures of Nrf2 activation in humans, yet less attention is placed on the regulation of these genes and its consequences.…”
Section: The Keap1/nrf2 Systemmentioning
confidence: 99%
“…Knockdown of Nrf2 in HepG2 cells led to a reduction of AKR7A3 mRNA and AKR7A3 protein and increased sensitivity to acetaminophen-induced cytotoxicity. 47 Analysis of the human AKR gene promoters identified the existence of multiple AREs in 13/15 human genes, and many have subsequently been found to be functional, Table 2. 46 …”
Section: Evidence That Human Akr Genes Are Regulated By Aresmentioning
confidence: 99%
“…Although much APAP is metabolized via conjugation with glucuronic acid and sulfate and then excreted, a portion of APAP is converted by cytochrome P-450 metabolism to a reactive quinone form, N-acetyl-p-benzoquinone imine (NAPQI), which is inactivated by conjugation with glutathione (GSH) [4]. Once the pool of GSH is exhausted, any remained N-acetyl-p-benzoquinone imine covalently binds cellular macromolecules induces a series of molecular events that include alkylation of proteins, membrane lipid peroxidation, mitochondrial dysfunction, imbalance of intracellular calcium, formation of reactive oxygen species and reactive nitrogen species [56]. APAP-induced hepatocellular damage and necrotic and apoptotic cell death can result in severe centrilobular hepatotoxicity and acute liver failure [78].…”
Section: Introductionmentioning
confidence: 99%